Experimental investigation of volcaniclastic compaction during burial - Zorn, Edgar U.; Kendrick, Jackie E.; Lamur, Anthony; Birnbaum, Janine; Kueppers, Ulrich; da Silva, Marize M.; Lavallée, Yan (Volcanica, 2024)
Volcanic deposits compact and deform following emplacement and burial. Here, we experimentally investigate the compaction of volcaniclastic material through gravitational loading (i.e. burial). Two lithologies (scoria and hyaloclastite) of different grain size (ash and lapilli) were held in a cylindrical container and compressed between two pistons to target stresses of 2, 5, 10, or 20 MPa, whilst monitoring axial displacement and acoustic emissions, enabling quantification of strain, densification, and comminution. In a second suite of experiments, samples were loaded and held at each stress to creep for six hours. The density and porosity of all samples were measured pre- and post-experiment. For all experiments, most deformation occurred during the early loading phase, then strain rates diminished with increasing compaction. During early loading, the hyaloclastite compacted faster than the scoria, but due to efficient early compaction, deformed more slowly at higher stresses and during creep. Grain size was also important for the amount of compaction; lapilli samples were initially less efficiently packed than ash samples and accumulated higher strain during the early part of loading. The strain experienced by all samples was substantial: even 2 MPa (equivalent to an overburden of 180–230 m for our porous lithologies) caused volume reductions of 10–30 % due to grain rearrangement and crushing. Interpolation and extrapolation of the data were used to forecast instantaneous and time-dependent surface deformation of volcaniclastic deposits of different thicknesses. The findings yield important new constraints for the interpretation of ground deformation signals and development of models of volcanic flank instability.